Multibeam bathymetry raw data (Kongsberg EM712 entire dataset) of RV MARIA S. MERIAN during cruise MSM130 - Achterberg, Eric Pieter; Streuff, Katharina Teresa; Schumacher, Mia (PANGAEA, 2024)
Raw multibeam bathymetry data were collected aboard RV MARIA S. MERIAN during cruise MSM130 POLAR BEAST using a Kongsberg 40-100kHz EM 712 multibeam echosounder with 0.5°x0.5° beam width. The expedition took place during 2024-07-09 - 2024-08-14 from Reykjavik to Reykjavik (Iceland) in the Northern Atlantic. Data were recorded in the EEZs of Greenland, Iceland and outside. The main objective of the MSM130 POLAR BEAST cruise are achieved through observations and modelling, and are: to investigate the role of Arctic sea ice loss as a driver of global change, (ii) to quantify chemical and physical processes at the ice- ocean-atmosphere interface that may constitute poorly-characterised climatic feedbacks in the Earth system. Sound velocity profiles (SVP) were applied on the data for calibration. Please see environmental data and the cruise report for details. The data are unprocessed and can therefore contain incorrect depth measurements (artifacts) if not further processed. Note that refraction errors may occur when no proper SVP is applied. Data acquisition was done by GEOMAR Helmholtz Centre for Ocean Research with funding for cruise logistics through the DFG (German Research Alliance). Provision of the data is supported by the DAM Underway Project and published according to the FAIR principles.
Keywords: Bathymetry; Multibeam Echosounder